Proving $(A \oplus B) \cap C = (A \cap C) \oplus(B\cap C)$

elementary-set-theorylogic

I'm trying to understand a proof that: $$(A \oplus B) \cap C = (A \cap C) \oplus(B\cap C)$$

So in the example, someone starts the proof from:
$$(A \cap C) \oplus(B\cap C)$$

and after a few steps got to the following:
$$((A \land C)\lor (B \land C )) \land (( \lnot A \lor \lnot C) \lor (\lnot B \lor \lnot C))$$
and then simplified it to:

$$((A\lor B) \land C)\land((\lnot A\lor \lnot B \lor \lnot C)) $$

I can see that to get from $$( \lnot A \lor \lnot C) \lor (\lnot B \lor \lnot C)$$ to $$(\lnot A\lor \lnot B \lor \lnot C)$$ the associative law and idempotent law has been applied to simplify.

However I can't figure out how to get from: $$(A \land C)\lor (B \land C )$$ to $$(A\lor B) \land C)$$

Many thanks!

Best Answer

This is distributive law, check this list of Logical equivalences might be helpful $${\displaystyle (\color{blue}q\wedge\color{red}p)\vee (\color{green}r\wedge\color{red}p)}\equiv (\color{blue}q\vee \color{green}r)\wedge\color{red}p\tag*{distributive law}$$ Hence $(\color{blue}A∧\color{red}C)∨(\color{green}B∧\color{red}C)\equiv(\color{blue}A∨\color{green}B)∧\color{red}C$ hold.